Veiled Hegemony: China’s Influence in BRICS through the Belt and Road - Muji , Benedictus Halleyando; Windiani, Reni (Journal of Law, Politic and Humanities, 2026)
This study analyzes China’s strategic use of the association of Brazil, Russia, India, China, and South Africa as an institutional platform to advance the Belt and Road Initiative and strengthen its influence in global governance. The research aims to explain how China consolidates hegemonic leadership through institutional mechanisms within the grouping. Using Antonio Gramsci’s theory of hegemony, the study conceptualizes dominance as operating through material power and ideological leadership. The research employs qualitative methods based on documentary analysis of official reports, summit declarations, and relevant literature. The findings identify three interconnected mechanisms. First, China promotes narratives of multipolarity and South–South cooperation to construct ideological leadership. Second, China institutionalizes its agenda through the New Development Bank, where infrastructure financing aligns with connectivity objectives of the Belt and Road Initiative. Third, China’s dominant economic position within the grouping generates structural dependencies that influence member states’ policy autonomy. The study concludes that this institutional synergy reconfigures, rather than eliminates, hegemonic structures in global governance through consensual arrangements.